José Leandro Fernandes - Launch Website - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2019)
José Leandro Fernandes, user engagement lead of SERVIR-Amazonia talks about the Program and invites users to go to the Website https://servir.ciat.cgiar.org/